Anestro pós-parto: luteólise prematura - Lima, Rafaela Sanchez de [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The prolonged postpartum anoestrus in cows reduces the number of calves leading to a significant economic loss to producers. Suckling and nutrition are the factors of great importance to the extension of the post-partum period. Besides, the occurrence of short cycles within 30 to 40 days postpartum contributes to an increase in the parturition–conception interval. These cycles are related to development of a corpus luteum with reduced duration after the first ovulation (less than 12 days). It is known that the short persistence of the corpus luteum is caused by advance of the luteolytic mechanisms. However, there is a lack of consensus regarding the cause of this anticipation. There are two currently accepted hypotheses, one related to the lack of prior exposure to progesterone, and the other related to the low concentration of pre-ovulatory estrogen. Considering the decrease in the incidence of short cycles in cows treated with progesterone and estrogen, the main protocols of ovulation induction include combination of both hormones. Therefore, this study aimed at describing the post-partum anestrous in cows and the main predisposing factors, emphasizing the first postpartum ovulation, short cycle and, its respective causes and consequences

O anestro prolongado pós-parto em vacas de corte reduz a produção de bezerros, causando uma perda econômica significativa aos produtores. Nestes casos, a amamentação e a nutrição são os fatores de maior importância para o prolongamento do anestro. Outro fator que contribui para prolongar o intervalo parto-concepção são os ciclos curtos que ocorrem durante os primeiros 30 a 40 dias pós-parto. Esses ciclos estão relacionados à formação de um corpo lúteo de duração anormal após a primeira ovulação (menor que 12 dias). Sabe-se que o corpo lúteo de curta duração é causado pela antecipação dos mecanismos luteolíticos, porém, ainda há controvérsias em relação aos motivos que levam a essa antecipação. São aceitas, atualmente, duas hipóteses, uma relacionada à falta de exposição prévia à progesterona e a segunda relacionada à baixa concentração de estrógeno pré-ovulatório. É observada uma diminuição na incidência de ciclos curtos em vacas em anestro tratadas com progesterona e estrógeno, por isso, os principais protocolos de indução da ovulação pós-parto incluem a associação de ambos os hormônios. O objetivo do presente estudo é descrever o anestro pósparto em vacas de corte e seus principais fatores predisponentes, dando ênfase à primeira ovulação pós-parto, ciclo curto, com suas causas e conseqüências.
Keywords: Reprodução animal; Anestro - vacas; Vacas de corte; Luteólise prematuro; Anoestrus - cowns